Pengaruh Ukuran Perusahaan, Struktur Kepemilikan Manajerial Dan Corporate Governance Terhadap Manajemen Laba (Studi Empiris pada Perusahaan Perbankan yang terdaftar di BEI Periode 2010-2014) - Sari, Okta Nofia, Drs. Eko Sugiyanto, M.Si (2016)
This study aims to test empirically the impact of firm size, ownership structure managerial, and corporate governance (audit committees and the board of commissioners) on earning management . Population of this study is companies registered in banking sector in Indonesian Stock Exchange during 2010-2014. This study used purposive sampling method to collect the sample. Based on certain, there were 31 go public companies that match as the sample. The analysis of statistic on this study used multiple regression analysis. In this study Discretionary Accruals as a proxy for earning management. Cross Sectional Modifed Jones' Model 1991 (Dechow et al 1995)has been used to determine earning management. The results of this study show that firm size have the significant effect on earning management, but the ownership structure managerial, and corporate governance (audit committees and the board of commissioners) have not the significant effect on earning management.